2019
DOI: 10.1186/s13052-018-0596-4
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal length and weight growth velocities according to Fenton reference and their associated perinatal factors in healthy late preterm infants during birth to term-corrected age: an observational study

Abstract: BackgroundOptimum early postnatal growth is critical for early and later health of preterm infants. Postnatal length and weight growth velocities and their associated perinatal factors in healthy late preterm infants without restriction of neonatal complications and nutritional problems have not been widely studied.MethodsAs part of ongoing longitudinal follow-up study of growth and development of preterm infants in Shandong Qianfoshan Hospital in China, 599 healthy late preterm infants without neonatal compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 40 publications
(49 reference statements)
5
59
5
1
Order By: Relevance
“…Zhang et al found that male preterms gained significantly more weight than females [6]. However, in our study, although the mean birth weight in male preterms was significantly higher than that of girls, no significant difference was found between the genders in terms of weight gain ratios within the first, 3rd, 7th, 15th and 30th days after birth.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Zhang et al found that male preterms gained significantly more weight than females [6]. However, in our study, although the mean birth weight in male preterms was significantly higher than that of girls, no significant difference was found between the genders in terms of weight gain ratios within the first, 3rd, 7th, 15th and 30th days after birth.…”
Section: Discussioncontrasting
confidence: 86%
“…This might be caused by the high rate of loss of the newborns due to the concomitant diseases. In addition, it was reported that mortality rates in those below 1500 grams would reach 60% [4][5][6]. In our study, this rate in the newborns below 1500 grams was found to be only 11.8%, which was significantly higher than the mortality rate (1.0%) in those over 1500 grams.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Vermont Oxford Network study reported that EUGR below the 10th percentile of weight by the Fenton growth chart occurred in half of VLBW infants [22]. The definition of EUGR as the change in z scores also has been used, and a study using the Fenton chart reported the prevalence of EUGR during NICU admission in preterm infants born at GA of 22-32 weeks as 47% in 2005 and 38% in 2012 [4,23]. EUGR defined by the Fenton chart in the present study seemed higher than those reports, but the study population was less mature in our study compared with those in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study noticed that growth trajectories of preterm infants were consistent over the WHO standards from CA 40 weeks to CA 24 months, especially for weight. Recent studies in Chinese population also found that growth rate in preterm infants was higher than that in term infants during the rst year of life (17,18). Several possible reasons might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 97%